Konceptutveckling av värmeinlägg för ammande kvinnor. En vidareutveckling på en lösning för att lindra mjölkstockning. - Ivarsson, Julia; Bengtsson, Stina (My University, 2025)
Breast engorgement is a common and painful condition affecting lactating mothers, often resulting from blocked milk ducts. Left untreated, it can lead to infections. One commonly recommended treatment is local heat application to improve milk flow and relieve discomfort. This project was conducted in collaboration with Allaiter Textile AB and Quokka AB to develop a more user-friendly and functional version of a heat insert for relieving symptoms of breast engorgement. The study applied a human-centered design process and involved both qualitative and quantitative methods, including interviews and surveys. Based on user feedback from prototype testing, several aspects of the existing product were identified as suboptimal, particularly regarding the handling of cables, the size of the power bank, and temperature control. A new concept was developed and evaluated using Pugh matrices and PNI analyses. The resulting design concept demonstrated improved usability, comfort and perceived effectiveness. The study concludes that a well-designed heat insert can support breastfeeding mothers both preventively and during acute engorgement, with potential for broader use in other stages of thematernal period and in an every-day usage.
Keywords: breast engorgement; lactation; user-centered design; maternal health; wearable heat therapy; product development; ergonomics; postpartum care; breastfeeding; thermal comfort.